‘Never again’? Resonances of the past in contemporary Aboriginal and Torres Strait Islander child removal - Anne Maree Payne (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
Kevin Rudd’s 2007 Apology to Australia’s Indigenous Peoples acknowledged the devastating impact of child removal on Aboriginal and Torres Strait Islander families and communities and included a commitment that ‘the injustices of the past must never, never happen again’ (Parliament of Australia 2008). Today however, while First Nations children comprise 6% of the total child population in Australia, they make up 41% of children in out-of-home care (SNAICC 2024b). This article explores the history of Aboriginal and Torres Strait Islander child removal during the Stolen Generations era, considering the ongoing impacts of this history on First Nations families today. While there have been changes, I identify significant continuities between past and contemporary child removal. These disturbing resonances of the past highlight the failed promise of Australian governments to deliver meaningful change in contemporary First Nations child removal policies and practices and to ensure that the mistakes of the past are not being repeated.